Generation of an induced pluripotent stem cell line (NCKDi006-A) from a 34-year-old patient with focal segmental glomerulosclerosis carrying a heterozygous mutation in the TRPC6 gene - Yiqing Wang; Minghao Yu; Zhihong Liu; Gang Wang (Stem Cell Research)
Focal segmental glomerulosclerosis (FSGS) is a common pathological nephrotic syndrome. The ion channel protein TRPC6 is associated mainly with the late-onset form of autosomal dominant familial FSGS. We identified a heterozygous mutation in the TRPC6 gene in an FSGS patient with a family history of end-stage renal disease (ESRD). Peripheral blood mononuclear cells (PBMCs) were obtained from the patient, and induced pluripotent stem cell (iPSC) lines were successfully generated. The establishment of these iPSC lines will provide a basis for further research into the pathogenesis of this condition.